The Manifestation of Malaysian Abstract Expressionist Art in the Context of Malaysian Modern Art (The Late 1950s-2010s) (Melayu: Jurnal Antarabangsa Dunia Melayu, 2024)
Malaysian Abstract Expressionist art has continued to impact and influence the nation’s art scene since the late 1950s. Malaysian artists such as Syed Ahmad Jamal, Yeoh Jin Leng, Latiff Mohidin and Chew Teng Beng have experimented and explored with abstraction in pursuit of their distinctive style, adding to the dynamic and ever-evolving context of Malaysian art. As the earliest proponents of Abstract Expressionist art in Malaysia, their influences are still strong today, as can be observed in the works of the following artists who achieved prominence in the Malaysian abstract art scene in the late 1970s: Sharifah Fatimah Zubir, Yusof Ghani, Rafiee Ghani, Suzlee Ibrahim and Awang Damit Ahmad. Thus, this paper aims to elucidate the connection between abstract art creativity and the aforementioned artists by examining the selected artworks produced by them. In this case, the domesticating strategy facilitated the transformation of Abstract Expressionism into the art creation of nine Malaysian artists, who used diverse abstraction approaches to convey their inner spirit. Based on the authors’ observation, the diverse abstraction trends bridge a connection between these two generations of Malaysian artists. Through the application of Edmund Felman’s visual analysis method, their works are observed to exhibit a variety of abstraction trends that have contributed to the diversification of Malaysian Abstract Expressionist art, which can be seen in gestural, pure, organic and calligraphic abstraction.Full text: PDF